Iron deficiency in the practice of a gynecologist: therapeutic efficacy - E. M. Dzhobava; I. G. Knysheva; D. P. Artizanova (IRBIS LLC, 2023)
Introduction. Iron deficiency (ID) of varying severity is the most common and rather serious extra-gynecological complication of adenomyosis resulting from meno/metrorrhagia of varying intensity, up to abnormal uterine bleeding requiring surgical hemostasis. Taking into account the chronic course of the disease, the complexity of radical therapy as well as a systemic effect ID also particularly affecting reproductive system, an issue of sufficient and timely ID correction in patients with adenomyosis of varying severity remains relevant.Aim: to study an efficacy of ID therapy with drug containing ferrous fumarate and folic acid in patients with adenomyosis.Materials and Methods. An observational study was conducted, which included 90 patients with isolated adenomyosis of varying severity: 30 patients with degree 1 adenomyosis (group 1), 30 patients with degree 2 adenomyosis (group 2), 30 women with degree 3-4 (group 3). All patients received ferrous fumarate plus folic acid for 30 days. To identify an ID variant, the level of serum ferritin, iron, transferrin, total iron-binding capacity of blood serum (TIBC), clinical blood test parameters such as hemoglobin level, erythrocyte count, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) were measured.Results. A significant increase in ferrokinetic parameters was found in all patient groups. The most significant and clinically important dynamics was noted for serum iron level and TIBC. For instance, after the therapy, the level of serum iron increased in group 1 from 11.0 ± 0.6 μmol/l up to 15.0 ± 1.1 μmol/l, in group 2 - from 9.0 ± 1.6 μmol/l up to 14 .0 ± 0.8 μmol/l, in group 3 from 7.0 ± 1.3 μmol/l up to 12.0 ± 1.3 μmol/l (p < 0.05). In addition, a decreased TIBC was found in group 3: from 68.0 ± 1.8 μmol/l down to 58.0 ± 1.7 μmol/l (p < 0.05); in groups 2 and 3 TIBC level tended to insignificantly decrease.Conclusion. The use of a preparation containing ferrous fumarate along with folic acid can effectively correct background ID of varying severity in patients with adenomyosis of varying intensity. An earlier and longer administration of iron preparations in patients with adenomyosis along with clinical and laboratory parameter monitoring is recommended to achieve more pronounced clinical effect.